2022
DOI: 10.1097/brs.0000000000004495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Literacy on Self-Reported Health Outcomes in Spine Patients

Abstract: Study Design. Cross-sectional survey study. Objective. The aim was to determine if health literacy level is associated with patient-reported outcomes and self-reported health status among patients presenting to an academic outpatient spine center. Summary of Background Data. Patient reports are critical to assessing symptom severity and treatment success in orthopedic spine patients. Patient-reported outcome measures (PROMs) are important instruments commonly used for this purpose. However, the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, a relationship between health literacy and self-reported health outcomes among new patients seen at an outpatient orthopaedic spine center has previously been demonstrated by Lans et al 4 When controlling for multiple confounding variables, their analysis revealed that patients with limited health literacy reported markedly worse baseline Patient-reported Outcome Measure Scores across seven different domains (Physical Function, Depression, Global Health-Physical, Global Health-Mental, Pain Interference, Pain Intensity, and Anxiety).…”
Section: Patient Perspectivesmentioning
confidence: 88%
See 1 more Smart Citation
“…However, a relationship between health literacy and self-reported health outcomes among new patients seen at an outpatient orthopaedic spine center has previously been demonstrated by Lans et al 4 When controlling for multiple confounding variables, their analysis revealed that patients with limited health literacy reported markedly worse baseline Patient-reported Outcome Measure Scores across seven different domains (Physical Function, Depression, Global Health-Physical, Global Health-Mental, Pain Interference, Pain Intensity, and Anxiety).…”
Section: Patient Perspectivesmentioning
confidence: 88%
“…3 Limited health literacy is associated with worse overall physical and mental health, inadequate self-management of chronic disease, higher mortality, higher rates of hospitalization, greater healthcare expenditure, and worse patientreported outcome measure scores. [4][5][6][7][8][9] The 2003 US Department of Education National Assessment of Adult Literacy survey found that 36% of the adult US population (approximately 87 million adults) had basic or below basic health literacy levels. 10 Unlike the intermediate literacy and proficiency literacy levels defined by the survey, basic literacy and below basic literacy levels are considered insufficient for function within the healthcare setting.…”
mentioning
confidence: 99%
“…Hence, identifying mechanisms to mitigate barriers of health literacy will be an important consideration for the physical collection aspect of clinically implementing PROMIS in orthopaedic settings both for clinical care and future outcomes research. This is critical as studies have shown that patients with low health literacy have worse patient-reported outcome scores within orthopaedic surgery, yet it is challenging for clinicians to recognize low health literacy in patients [18,21,37]. Furthermore, there is a paucity of research on health literacy in the context of orthopaedic surgery outcomes even though prior work has shown that limited musculoskeletal health literacy is more common than general health literacy, especially among patients with lower levels of education and minority identities [22,29].…”
Section: Is Health Literacy Associated With Completion Of Promis Cat?mentioning
confidence: 99%
“…4 Limited ability to understand reading materials, patient education, discharge instructions, and informed consent all adversely affect the continuum of care. [5][6][7][8][9] This costs the American health system an estimated 106 to 208 billion dollars annually. 10 Despite widespread inadequate health literacy, this limitation in health care is not routinely evaluated by health care practitioners.…”
mentioning
confidence: 99%
“…11 Moreover, these patients were significantly more likely to report worse baseline PROMs and general health. 6 Although the literature is limited, the majority of PROM questionnaires are written above the average reading level of the targeted population. 12,13 Readability is an important component of health literacy.…”
mentioning
confidence: 99%